An update on the knowledge and general understanding of the Chilean Diptera diversity - Barahona-Segovia, Rodrigo M.; Madriz, R. Isaí; González, Christian R.; Amorim, Dalton De Souza (Zootaxa, 2024)
Chilean flies play an important role in many aspects of phylogeny and evolution of Diptera given their uniqueness and direct link with the Gondwanan insect fauna. Many dipterists have considered the order to be one of the most diverse in Chile, but there are still many gaps of information to fill. This study updates the families, genera, and species known from Chile and addresses the evolutionary origin of most dipteran families—indicating which biogeographical layers they belong to. The taxonomic literature was thoroughly reviewed from 1967 until May 2024. Our investigation revealed a total of 97 families, 930 genera and 4,108 valid species, placing Diptera as one of the most specious insect orders in Chile. The diversity of the Lower Diptera (suborders Tipulomorpha, Psychodomorpha, Culicomorpha, Perissommatomorpha and Bibionomorpha) increased to 111 genera (93.27%) and 1,019 species (136.22%), whereas Brachycera increased to 229 genera (48.61%) and 703 species (50.72%). Specifically, the number of genera and species in the division Aschiza increased by 117.14% and 114.28% respectively, while Acalyptratae increased by 62.24% genera and 63.82% species to date. Finally, the number of genera and species in the Calyptratae increased by 31.05% and 50%, respectively. The family Neriidae is newly recorded for Chile and the species Telostylinus lineolatus (Wiedemann) is reported from Easter Island. We present age hypotheses of clades in Chile belonging to 60 families—of which 16 correspond to Cretaceous- and 46 to Cenozoic-, and a small number to Jurassic-elements. Finally, we address three major gaps for a more robust development of Diptera systematics in Chile: (1) lack of long-term systematic sampling, (2) taxonomic, spatial, and temporal biases for Diptera diversity and (3) poor understanding of biological and ecological processes related to Diptera facing advances in anthropogenic impacts across the country.